PELABELAN SUPER MEAN PADA GRAF ð‘«ð’(ð‘ªðŸ‘) DAN ð‘«ð’(ð‘ªðŸ‘) v ð‘·ð’• - Wahyuningsi, Sri; Sudarsana, I Wayan; Musdalifah, Selvy (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2015)
PELABELAN SUPER MEAN PADA GRAF ð‘«ð’(ð‘ªðŸ‘) DAN ð‘«ð’(ð‘ªðŸ‘) v ð‘·ð’•